"After this presentation I feel more confident caring for autistic patients": The impact of neurodivergent doctors educating hospital staff about neurodiversity - Bernard, Sarah; Teasdale, N.; Harris, Courtenay; Girdler, Sonya (2025)
Guidelines for professionals practising in healthcare settings recommend that autistic people seeking care should receive neurodiversity-affirming support. However, education on neurodiversity is not widely included in health professional training in Australia. With a focus on health equity for autistic, neurodivergent people, we conducted a healthcare improvement initiative addressing the need for neurodiversity education in an Australian tertiary hospital through a change process. This project was conducted from May to November 2022, led by neurodivergent, disabled doctors who developed neurodiversity education for two hospital departments, refined through Plan-Do-Study-Act cycles and feedback surveys. The feedback survey, which included an opportunity to provide comments, was completed by 29 of 44 attendees, a response rate of 66%. Respondents agreed the education was relevant to their work (97%, n = 28), and reported more confidence (83%, n = 24) and acceptance (90%, n = 26) of autistic patients and colleagues. Themes identified in the analysis of the open-ended questions included reducing negative attitudes (biases), recognizing unmet neurodiversity learning needs, and a shift in perspective. Neurodivergent doctors led this healthcare improvement project to educate hospital clinicians about neurodiversity. The theme of reducing bias emerged from the open-ended responses, highlighting the importance of this work, given bias contributes significantly to health inequity.